Literasi Digital Anak dalam Menggunakan Media Sosial TikTok: Studi Kasus Fungsi Pengawasan Media Sosial TikTok pada Siswa Kelas 6 SDIT Anni’mah - Azka Muhammad Razaka; Santi Indra Astuti (Bandung Conference Series: Public Relations, 2023)
Abstract. The purpose of this study was to find out the supervision of parents and teachers in the use of social media TikTok on children in the 6th grade students of SDIT Anni'mah based on 4 aspects of digital literacy formulated by the Ministry of Communication and Informatics, namely digital skills, digital ethics, digital safety, and digital culture. This study uses a qualitative method with a case study approach to describe facts systematically based on the results of interviews, observations, and documentation in the field with the parents and teachers of SDIT Anni'mah who are the subjects of this research. The data were analyzed using data reduction analysis techniques, data presentation, and conclusion drawing, as well as triangulation to ensure the validity of the data. The results of the study show that children/students in the four aspects of digital literacy have been able to fulfill three of them, namely digital skills, digital ethics, and digital culture. Students have not been able to fulfill one of the four aspects of digital literacy, namely digital safety because children/students have not been given an understanding of this from both the teacher and their parents, it's just that parents and teachers have carried out monitoring activities for children by using the notification feature which provided by TikTok so that every child who uploads content, a notification will appear on the parent's account. Parents and teachers also supervise by occasionally looking at children's smartphones to find out what activities children are doing on social media TikTok. Abstrak. Tujuan penelitian ini untuk mengetahui pengawasan orang tua dan guru dalam penggunaan media sosial TikTok pada anak di lingkungan siswa kelas 6 SDIT Anni’mah berdasarkan 4 aspek literasi digital yang dirumuskan oleh Kementerian Komunikasi dan Informatika yaitu digital skills, digital ethics, digital safety, dan digital culture. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kasus untuk mendeskripsikan fakta-fakta secara sistematis berdasarkan hasil wawancara, observasi, dan dokumentasi di lapangan dengan orang tua murid dan guru SDIT Anni’mah yang menjadi subjek penelitian ini. Data dianalisa dengan menggunakan teknik analisis reduksi data, penyajian data, dan penarikan kesimpulan, serta dilakukan triangulasi untuk memastikan keabsahan data. Hasil penelitian menunjukan bahwa anak/murid dalam keempat aspek literasi digital sudah mampu memenuhi tiga diantaranya yaitu digital skills, digital ethics, dan digital culture. Murid belum mampu memenuhi salah satu dari keempat aspek literasi digital yaitu digital safety karena anak/murid belum diberi pemahaman mengenai hal ini baik dari guru maupun dari orang tuanya, hanya saja orang tua dan guru sudah melakukan kegiatan pengawasan pada anak dengan cara menggunakan fitur notifikasi yang disediakan oleh TikTok sehingga setiap anak yang mengunggah suatu konten, maka akan muncul notifikasi di akun orang tua. Orang tua dan guru juga mengawasasi dengan cara sesekali melihat smartphone anak untuk mengetahui kegiatan yang anak lakukan pada media sosial TikTok.